Estrutura genética de populações de Scinax granulatus (Peters) (Amphibia, Anura) de Bromeliaceae do Refúgio da Vida Silvestre dos Campos de Palmas (PR) - Kuhn, Sama Beatriz (2014)
The studies about anuran amphibians have generate interest of several researchers due the presence of these animals in almost the entire planet, its easy handling, and mainly because they are good indicators of ecological balance. The knowledge of the genetic variability status and its spatial and temporal distribution are essential for accurate analysis and detection of potential threats to a species. In the latest years, the integration of information provided by nuclear and mitochondrial markers have become recurrent, since they have different rates of evolution. The Scinax granulatus, like other amphibians, is widely distributed and can be considered as bio-indicator of environmental quality. Through the use of molecular markers ISSR (Inter Simple Sequence Repeat) and amplification of mitochondrial DNA D-loop, this study aimed to determine the genetic diversity and population structure of S. granulatus on a lagoon at the Refugio de Vida Silvestre dos Campos de Palmas - PR. From the 28 sampled individuals, those one`s from A-side of the lagoon formed a single group (Side A) (n=8), and side B individuals were divided into 3 groups, as they were collected in bromeliads on different tree: Side B - Bromeliad 1 (n= 0), Side B - Bromeliad 2 (n=5) and Side B - Bromeliad 3 (n=5). The total DNA was purified and analyzed by nuclear ISSR marker and the mitochondrial DNA D-loop was amplified. The nuclear marker was highly polymorphic in all subpopulations, whereas 95.02% of the genetic variation was intrapopulation and 4.98% interpopulation. There was a high occurrence of gene flow between both sides of the lagoon, since there was no significant differentiation between these subpopulations. The index of interpopulation genetic differentiation exhibited moderate values for the population Side B - Bromeliad 3 in relation to the others, where Fst ranged 0.064-0.109, which may be related to reproductive behavior and development of these amphibians in bromeliads, which are excellent micro-habitats. The amplification of mitochondrial DNA D-loop showed three fragments of different lengths, which is the first indication of the occurrence of heteroplasmy in neotropical frogs. Although it still need more detailed studies, the results of this research will enable the development of an appropriate management plan in order to ensure the maintenance of the levels of genetic diversity of S. granulatus.